Oligella Infections: Case Report and Review of the Literature - Mahin Baqi; Tony Mazzulli (Canadian Journal of Infectious Diseases)
A case of Oligella ureolytica infection of a cervical lymph node is presented and previous cases of oligella infection reported in the literature are reviewed. Underlying malignancy and urinary tract obstruction were observed in many of the cases. All patients responded to antimicrobial therapy and, in those cases associated with urinary tract obstruction, surgical relief of the obstruction. The microbiology and clinical features of oligella infections are reviewed.